2014
DOI: 10.1097/dcr.0000000000000025
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the Challenges of Primary Tumor Management in Patients With Metastatic Colorectal Cancer Unresectable for Cure and an Asymptomatic Primary Tumor

Abstract: Approximately 75% of upfront chemotherapy patients with unresectable, asymptomatic stage IV colorectal cancer can be spared initial resection of the primary tumor. Colonoscopic findings of nontraversable lesions at diagnosis may predict the need for late surgical intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 16 publications
1
27
1
6
Order By: Relevance
“…They found that nontraversable lesions had higher 2-year rates of symptomdirected surgery than those with colonoscope-traversable lesions (64.3 vs 9.9 %). Moreover, the median time until symptom-directed surgery was significantly lower in colonoscopic non-traversable tumours (2.1 vs 15.5 months; p=0.01) [17]. Miyamoto et al found that patients with circumferential tumours were likely to suffer an obstruction during chemotherapy treatment [18].…”
Section: Discussionmentioning
confidence: 99%
“…They found that nontraversable lesions had higher 2-year rates of symptomdirected surgery than those with colonoscope-traversable lesions (64.3 vs 9.9 %). Moreover, the median time until symptom-directed surgery was significantly lower in colonoscopic non-traversable tumours (2.1 vs 15.5 months; p=0.01) [17]. Miyamoto et al found that patients with circumferential tumours were likely to suffer an obstruction during chemotherapy treatment [18].…”
Section: Discussionmentioning
confidence: 99%
“…Initialement compris entre 9 et 30 %, ces taux provenaient d'études comprenant des patients traités avec d'anciens protocoles de chimiothérapie [6][7][8][11][12][13][14][15][16]. Dans les études plus récentes dans lesquelles les patients étaient traités par des chimiothérapies efficaces (oxaliplatine, irinotécan, biothérapies), ce risque était moindre, compris entre 11 et 22 % [9,10,[17][18][19][20]. Ces résul-tats pourraient s'expliquer par le fait que les chimiothé-rapies de nouvelle génération ont également une importante efficacité antitumorale sur la TP et permettent un meilleur contrôle local en cas de tumeur laissée in situ [21].…”
Section: Taux De Complications Liées à La Tp Au Cours D'une Chimiothéunclassified
“…Dans la littérature, 17 études rétrospectives et deux études de cohorte ont évalué l'impact de la colectomie première sur la survie de patients avec un CCR métastatique avec méta-stases synchrones non résécables, avec un total de 5 555 patients (Tableau 3) [6][7][8][9]11,[13][14][15][18][19][20]23,26,[34][35][36][37][38][39]. Douze études concluaient à une augmentation significative de la SG lorsque la prise en charge débutait par la résec-tion de la TP [7][8][9]13,23,26,[34][35][36][37][38][39].…”
Section: Impact De La Résection De La Tp Sur La Survie Chez Les Patieunclassified
See 2 more Smart Citations